The impact of perceived caregiver anxiety and stress during childhood on late-life depression: evidence from the China Health and Retirement Longitudinal Study - Jin, Liuyin; Wang, Dongdong; Yang, Dengxian; Jin, Qiong; Cao, Mengye; Li, Yuanyuan; Yang, Jiajie; Xie, Guoming; Zhang, Wenwu (Frontiers in Psychiatry, 2025)
IntroductionThis study investigates the long-term impact of perceived caregiver anxiety and stress during childhood on late-life depression. Adverse childhood experiences related to caregiver mental health may significantly influence emotional well-being, and this study utilizes data from the China Health and Retirement Longitudinal Study (CHARLS) to explore these associations.MethodsCHARLS data were analyzed for individuals who reported perceived caregiver anxiety and stress. Depression was measured using the CES-10 depression scale. Multivariate logistic regression models examined the relationship between caregiver anxiety and stress frequency and late-life depression, adjusting for confounders like socioeconomic status, health behaviors, and demographics.ResultsChildhood exposure to caregiver anxiety and stress significantly increased the risk of depression in later life (p < 0.05), with stronger effects observed among individuals with female caregivers. The risk escalated with the frequency of caregiver anxiety episodes. After adjusting for covariates, the association for male caregivers weakened, highlighting the potential role of other mediators.DiscussionThe results highlight the critical importance of parental mental health, especially maternal anxiety, in mitigating intergenerational mental health risks. Targeted interventions for caregiver mental health, particularly for female caregivers, are crucial. Longitudinal studies are needed to better establish causality and further investigate these mechanisms.